Epipactis helleborine (L.) Crantz subsp. moratoria A. Riechelmann & A. Zirnsack., a new subspecies of Broad-leaved Helleborine in Slovenia - Lipovšek, Matej; Brinovec, Tadeja; Brinovec, Marina (Hacquetia, 2016)
The group of Epipactis helleborine s.l. includes several subspecies. A new subspecies Epipactis helleborine subsp. moratoria was determined in Slovenia in 2015. It thrives in mixed wood in a region of Gorica at Raztez. Morphologic and phenomenological comparison confirmed clear differences between E. helleborine subsp. moratoria and E. helleborine subsp. helleborine. The characteristic differences seen in E. helleborine subsp. moratoria are the stem which is more or less bent at the level of the leaf base, the plants are smaller and more slender than E. helleborine, there are also differences in the flowers and the leaves. The ovary in E. moratoria is often in a horizontal position, especially at the time of fruiting, wheras in E. helleborine ovary usually hangs down. All of the wild orchids in Slovenia are protected species and among them it is Epipactis helleborine subsp. moratoria which, up till now is only known at one site.